(untitled) (Journal Resuscitatio Balcanica, 2024)
Aims: . The analysis aimed to investigate differences in the initiation of cardiopulmonary resuscitation based on gender, as well as differences between geneders considering location of the cardiac arrest, etiology, and age. Material and methods: This study analyzed epidemiological data on out-of-hospital cardiac arrest from the EuReCa study, collected via the European Resuscitation Council and EuReCa ONE protocol. The dataset, covering October 1, 2014, to December 31, 2021, was created using data from 16 municipalities in Serbia, representing 24.13% of the population. Results: Data revealed a total of 8,349 OHCA cases, with CPR initiated in 2,758 cases (33.1%). Statistically significant differences in CPR initiation were observed between genders, with a higher initiation rate for males (41.7%) compared to females (23.5%) (χ2 (1) = 307.312; p<0.001). Initiation rates were higher for males across all locations of arrest, including residence and non-residence settings, and for various etiologies, particularly cardiac causes (χ2 (1) = 186.341; p<0.001). Age-related differences were significant for those over 65, with CPR initiation less frequent in females compared to males (χ2 (1) = 244.642; p<0.001). Conclusion: The findings indicate a gender disparity in CPR initiation. These results highlight the need for tailored resuscitation guidelines to address gender disparities and improve outcomes for all patients experiencing OHCA. Further research is required to explore underlying factors contributing to these differences and to refine resuscitation protocols.